COLONOSCOPIC EXAMINATION PROFILE AT THE UKI HOSPITAL, EAST JAKARTA FROM JANUARY 2014 - JULY 2015 - Simanjuntak, Tiroy Sari B. (International Journal of Research -GRANTHAALAYAH, 2021)
Colonoscopy is a procedure, which is done using a Colonoscope. The technique implemented in evaluating the colon: Picture of the colon, derived from the computed tomography or magnetic resonance imaging, is processed (reconstructed) by the computer to reveal colon lumen in 3D. Colonoscopy is used to diagnose diseases found in the large intestine; however, not all kinds of ailments in the large intestine can be diagnosed by colonoscopy. This study aims to determine the colonoscopy procedure profile in UKI Hospital East Jakarta from 2014 to July 2015. The design used by this research is a descriptive study, which is retrospective to the population of patients that have had a colonoscopy in UKI Hospital from January 2014 to July 2015. This study reveals the colonoscopy procedure profile at UKI Hospital, East Jakarta from January 2014 to July 2015: the most dominant age of the patients receiving colonoscopy is between 50 and 59. Patients are males of Batak ethnicity with a background of high school education. These males' main symptom is abdominal pain, which leads to colitis infection as the primary diagnosis. This study shows that patients who have the colonoscopy done upon them are patients with the age span of 50–59. Most are males due to the factor of lifestyle and stress condition. Background of the patients is working males with high school diplomas. The main complaint found among these patients is abdominal pain. Colitis infection is found to be the primary diagnosis among them.